A Fair Version of the Chinese Room - Çağatay, Hasan (Problemos, 2019)
By the Chinese room thought experiment, John Searle (1980) advocates the thesis that it is impossible for computers to think in the same way that human beings do. This article intends firstly to show that the Chinese room does not justify or even test this thesis and secondly to describe exactly how the person in the Chinese room can learn Chinese. Regarding this learning process, Searle ignores the relevance of an individual’s pattern recognition capacity for understanding. To counter Searle’s claim, this paper, via examining a series of thought experiments inspired by the Chinese room, aims to underline the importance of pattern recognition for understanding to emerge.